The defector : a novel - Hadfield, Chris, 1959- (Mulholland Books, an imprint of Little, Brown and Company, 2023)
In 1973 Israel, as the Yom Kippur War erupts and a state-of-the-art Soviet MiG fighter makes an unexpected landing, NASA Flight Controller and former U.S. test pilot Kaz Zemeckis is drawn into a high-stakes game of spies, lies and secrets that hold the key to Cold War air and space supremacy.